A clinical analysis of sub-fertile women undergoing diagnostic laparoscopy and hysteroscopy - Sahu, Ekta; Modi, Jyoti Nath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Diagnostic laparoscopy and hysteroscopy are considered the gold standard for diagnosing pelvic pathology in women among couples with infertility or subfertility. Knowledge of common pathologies in these patients would help plan investigations and deliver better care especially in resource limited settings. The current study was carried out to analyse the clinical-demographic profile and operative findings among women with subfertility undergoing diagnostic laparoscopy-hysteroscopy over a 4 years period. Methods: A retrospective record-based study conducted in the Department of Obstetrics and Gynaecology of People’s Hospital, PCMS and RC, Bhopal from 1st January 2013 to 31st December 2016 (4 years). Results: Sixty-two records of women with primary/ secondary infertility who underwent diagnostic laparoscopy-hysteroscopy during the study period satisfied the inclusion and exclusion criteria and were analyzed. Among these, 54 (87.09%) couples had primary infertility and 8 (12.9%) had secondary infertility. The mean age of women was 27.1 years (range 20-38 years; SD4.43). One third of women had more than 5 years duration of infertility. Eight (13%) had menstrual abnormalities. One or more tubal abnormality was found on diagnostic laparoscopy in 33.8% of all cases (31.4% of women with primary infertility and 50 % of women with secondary infertility). Pelvic adhesions (25.8%), endometriosis (24.2%) and evidence of acute or chronic pelvic inflammatory disease (19.3%) were the other leading abnormalities. Conclusions: While it is possible to suspect many abnormalities by a detailed history, a good examination and preliminary investigations such as the pelvic ultrasonography, a significant proportion of abnormalities such as the tubal abnormalities, endometriosis and pelvic adhesions can only be detected with certainty on laparoscopy. Hence it is recommended that diagnostic laparoscopy should be an early part of infertility work up.